The Defamation of Debt Posts on Social Media Accounts (Study of Medan District Court Decision NO. 3563/PID.SUS/2019/PN MDN) - Fauzi, Masyhurul; Ginting, Elvira Dewi (Jurnal Daulat Hukum, 2024)
This study aims to analyze Medan District Court 3563/PID.SUS/2019/PN MDN related to the defamation case of Febi Nur Amelia who posted Fitriani Manurung's debt on a social media account. This research uses normative legal methods. The results showed that based on the Judge's decision number 3563/PID.SUS/2019/PN MDN, it was stated that the Defendant Febi Nur Amelia was not proven guilty of committing the crime of defamation as alleged by Fitriani Manurung through the charges at trial. As well as what has been proven, that the case is not included in the criminal act of defamation, because indeed what Febi Nur Amelia has done by posting debts on her social media account, namely through Instagram stories, is intended so that Febi's friend who is also a friend of Fitriani sees the post and tells her to the person concerned, namely Fitriani Manurung to immediately pay her debt, this was done by Febi because she could not contact Fitriani, because access such as her number and social media account had been blocked. Judges need to understand the background of the criminal offense in their decisions. To overcome juridical obstacles, adequate resources and reliable knowledge are needed for law enforcement officials, as well as sufficient budget for law enforcement facilities. The public also needs to receive legal education from law enforcement officials in dealing with legal issues.